NOVEL QUERCETIN GLYCOSIDE WITH PROMISING HEPATOPROTECTIVE ACTIVITY ISOLATED FROM LOBULARIA LIBYCA (VIV). C.F.W. (BRASSICACEAE) - Ayoub, Nahla; Nematallah, Khaled A.; Al-Gendy, Amal A.; Zaghloul, Soumaya S. (European Scientific Journal, ESJ, 2013)
A novel flavonoid compound characterized as Quercetin 3-O-α-L-rhamnopyranosyl (1’’’→4’’)-β-D-galactopyranosyl-7-O-α-L-rhamnopyranoside was isolated from the n-butanol fraction obtained from the ethanolic extract of Lobularia libyca (viv). C.F.W. (Brassicaceae). Also, two known flavonoids characterized as quercetin and kaempferol were isolated from the ethyl acetate fraction obtained from the ethanolic extract of the plant. The structure of the novel compound was established on the basis of extensive spectral and chemical studies. The complete spectral assignments of the isolated compounds are reported here on the basis of 1D (1H and 13C) and 2D (HMBC) NMR, high resolution mass (HRMS) spectroscopic data and UV spectral analysis. The results show that the n-butanol fraction has a promising antioxidant activity measured by 1,1-dipheny1-2-picrylhydrazine (DPPH) method with IC50 = 10.49 μg/ml. Moreover the hepatoprotective activity of the n-butanol fraction as well as the new compound was studied using in-vitro technique by using human liver cell lines and measuring specific enzymes which are alanine transaminase (ALT), aspartate transaminase (AST), glutathione (GSH) and superoxide dismutase (SOD). The best activity was observed at concentration 0.1 mg/ml of the n-butanol fraction. The fraction as well as the novel compound exhibit a promising hepatoprective activity comparable to a reference standard silymarin.